Pliocene hominin biogeography and ecology. Issue 87 (October 2015) - Macho, Gabriele A.
Abstract: Australopithecus bahrelghazali, its origin and palaeobiology are not well understood. Reported from only one location some several thousand kilometres away from East African Pliocene hominin sites, it appears to have predominantly fed on C4 sources. Yet, it lacks the morphological adaptations of other primate C4 consumers like Paranthropus boisei and Theropithecus oswaldi . Furthermore, although considered to belong to Australopithecus afarensis by most researchers, A. bahrelghazali appears to differ from the former in a key aspect of its morphology: enamel thickness. To assess the phylogeny and palaeobiology of A. bahrelghazali, I first evaluate the dietary adaptations and energetics of A. bahrelghazali using empirical data of the feeding ecology of extant baboons, Papio cynocephalus . Information published on A. bahrelghazali morphology and habitat preference is used to select C4 foods with the appropriate mechanical properties and availability within the environment to create the models. By altering the feeding time on various food categories, I then test whether A. bahrelghazali could have subsisted on a C4 diet, thus accounting for the δ 13 C composition of its dental tissue. The effects of body mass on the volume of food consumed are taken into account. The outcomes of these simulations indicate that A. bahrelghazali could have subsisted on a diet of predominantly sedges, albeit with limitations. At higher energy requirements, i.e., above 3.5 times the BMR, it would be difficult for a medium-sized primate to obtain sufficient energy from a sedge-based diet. This is apparently due to constraints on foraging/feeding time, not because of the nutritional value of sedges per se. These results are discussed against the backdrop of A. bahrelghazali biogeography, palaeoenvironment, and phylogeny. The combined evidence makes it plausible to suggest that Northern Chad may have been a refugium for migrating mammals, including hominins, and throws new light on the deep history of A. bahrelghazali .